PENERAPAN ACTIVITY BASED COSTING UNTUK MENENTUKAN HARGA POKOK PRODUKSI PADA PT. GUNUNG GAHAPI SAKTI ADALAH PERHITUNGAN HARGA POKOK PRODUKSI DENGAN SISTEM TRADISIONAL PT. GUNUNG GAHAPI SAKTI MEDAN - Zainal Abidin; Yulianty Yulianty (Universitas Medan Area, 2015)
The aim of this study is to investigate the calculation of Cost of Products by using Activity Based Costing at PT. Mount Gahapi Way Belawan and compare the calculation of Cost of Products at PT by using Traditional System and Activity Based Costing. For the research done using the descriptive method by arranging and classifying the data, analyzed then interpreted in order to obtain a clear picture of the object studied. The comparison of the calculation of Cost of Production with Traditional System and Activity Based Costing for variations in the size of 30.40 and 50 respectively is Rp. 405.74 (2.45%), Rp. 379.18 (2.39%) and Rp. 1949.42 (17.38%). That is the traditional system, to variations of elbow sizes 30 and 40 occurs overcost when compared with Activity Based Costing, whereas for products with variations in the size of the elbow 50 by calculation with Traditional Openness has occurred undercost when compared with the calculation of the Activity Based Costing.